Sundanese Sufi and Religious Diversity in the Archipelago: The Pluralistic Vision of Haji Hasan Mustapa (1852-1930) (Kawalu: Journal of Local Culture, 2024)
The paper aims to analyze moderate understanding of Haji Hasan Mustapa on religious diversity in the archipelago. He is a greatestSundanese poet who has studied in Mecca and served as Hoofd Penghuluof Kotaraja Aceh and Bandung in the colonial era. This study is focused onsufism and religious diversity, Mustapa‟s scholarship, and on his pluralisticvision, using intertextual studies and semantic analysis. This research arguesthat Mustapa has tolerance and moderate understanding similarly with Ibn„Arabi‟s thought. He uses kernel and husk as symbolic images whichexpressed using natural richness of Sundanese culture for demonstrating hisreligious conviction that rasa is the kernel of all religions. This study issignificant for strengthening the discourse of religious pluralism from sufiperspective in the archipelago which cannot be separated from the chain ofIslamic intellectual network. This research has also a significant impact onChittick‟s assumption about the depth of sufi poetry which mostly revealtheir tolerance views on religious diversity living in harmony.